Simultaneous measurement of multiple variant-specific SARS-CoV-2 neutralizing antibodies with a multiplexed flow cytometric assay - Liu, Hong; Varvel, Stephen; Chen, Ge; McConnell, Joseph; Caffrey, Rebecca; Galdzicka, Marzena; Shabahang, Shahrokh (Frontiers in Immunology, 2022)
Introduction Neutralizing antibodies (NAbs) have been recognized as surrogates of protection against SARS-CoV-2; however, the emergence of variants/subvariants escaping neutralization suggests that laboratory assessments of NAbs against the ancestral/wild type (WT) antigens likely overestimate the degree of protection. Methods A novel flow cytometry-based multiplex test system was developed for the simultaneous detection of NAbs of multiple SARS-CoV-2 variants. SARS-CoV-2 antibodies (Abs) including IgG, IgM, IgA isotypes were measured in the same system. Samples from negative, convalesced, vaccinated, boosted, and breakthrough infection (BTI) populations were tested for both NAbs and Abs. Results NAbs induced by WT showed neutralization activity that correlated strongly to all variants (R2 > 0.85) except omicron BA.1/BA.2 (R2 <0.50). Two doses of vaccine elicited very little protective immunity against BA.1/BA.2, though a booster dose significantly improved NAbs for all variants. NAbs/Abs increased more following BTI than after a booster, suggesting that hybrid immunity (vaccination + natural immunity) was more robust to all variants including BA.1/BA.2. BTIs occurring in the omicron era led to stronger NAb responses against BA.1/BA.2 than did older BTIs. In all comparisons, the RBD antigens demonstrated greater differences between WT and BA.1/BA.2 than the spike antigens. Discussion Taken together, we demonstrated that both Ab and NAb against multiple SARS-CoV-2 variants/subvariants can be reliably detected on the same multiplex platform. Distinguishing NAbs to the appropriate antigenic target of prevalent variants offers the best correlate of protection and aids individual decisions about the appropriateness and cadence of vaccine boosters and other exposure mitigation strategies.